Anti-adhesion molecule therapy as an interventional strategy for autoimmune inflammation. - Lockwood, C; Elliott, J; Brettman, L; Hale, G; Rebello, P; Frewin, M; Ringler, D; Merrill, C; Waldmann, H (1999)
Functional inactivation of leukocyte adhesion molecules has been used to intervene in the development of tissue injury in experimental models of postperfusion infarction as well as autoimmune inflammation. We investigated the use of humanized monoclonal antibodies (mAb) against CD18 in the treatment of five patients with vasculitic tissue injury sufficient to threaten infarction or gangrene. The treatment was monitored in three ways: (i) whole-body gamma camera scintiscanning of autologous indium-labeled PMN, (ii) an index of the therapeutic inhibition of adhesion derived from comparison pre, during, and post mAb treatment of the ability of patients' PMN to be aggregated after activation by fMLP, and (iii) flow cytometric analysis of PMN CD18 expression. Four of five patients given anti-CD18 at 20 mg/day for up to 3 weeks showed prompt clinical improvement, with healing of the ulceration and restoration of limb function within 4 weeks, which was sustained. The fifth patient, who was not doing well clinically, decided to withdraw from all active treatment: at autopsy there was no evidence of the underlying vasculitis evident pretreatment. Our findings suggest that anti-adhesion molecule treatment might be an effective immediate treatment in severe vasculitis especially when tissue viability is threatened by progressive infarction and/or development of gangrene.